Pharmacokinetics of mebendazole in plasma and cerebrospinal fluid following a single oral dose in healthy dogs - Yanke, Amy B.; Day, Kendall E.; Taylor, Amanda R.; Cruz-Espindola, Crisanta; Boothe, Dawn M. (Frontiers in Veterinary Science, 2023)
Novel therapies are needed for treatment of gliomas. Mebendazole previously demonstrated anti-neoplastic effects on canine glioma cell lines at in vitro mean inhibitory concentrations (IC50) of 10 ng/mL. Our study aimed to titrate the oral dose of mebendazole necessary to achieve concentrations ≥10 ng/mL in cerebrospinal fluid (CSF) of healthy dogs. We hypothesized that an oral dose up to 200 mg/kg would be necessary. Phase one was a dose titration study using a total of 6 mixed breed dogs that described dose vs. plasma concentrations for 72 h after single oral dosing of either 50 mg/kg (n = 2), 100 mg/kg (n = 2), or 200 mg/kg (n = 2). Based on phase one, phase two dogs (total of 9) received 100 mg/kg (n = 4) or 200 mg/kg (n = 5) orally and blood samples were collected intermittently for 60 h with CSF samples collected intermittently for 24 h. Mebendazole was quantitated in plasma and CSF using high performance liquid chromatography. Median peak plasma concentrations (Cmax) were reached at 7 ± 2 h (100 mg/kg) of 220 ng/mL (81, 283) and at 15 ± 4 h (200 mg/kg) of 147 ng/ml (112, 298). The respective area under the curve (AUC: ng/ml/h) reported as a median was 2,119 (1,876, 3,288) vs. 3,115 (1,559, 4,972). Median plasma concentrations (ng/ml) for 100 vs. 200 mg/kg were 47 (32, 52) vs. 65 (35, 104), respectively. For CSF, the median value for Cmax (at 100 mg/kg vs. 200 mg/kg) was 8 (2, 28) vs. 21 (12, 27) and AUC was 87 (22, 157) vs. 345 (92, 372), respectively. Relative bioavailability in CSF vs. plasma was 4 to 10%. Although several animals demonstrated clinical signs indicative of gastrointestinal upset [i.e., vomiting (n = 2), diarrhea (n = 2), or both (n = 1)], these events were not considered serious. The in vitro IC50 for gliomas can be reached in CSF at 100 mg/kg (n = 1), however a 200 mg/kg dose yielded more consistent concentrations.